Dialektika Pemikiran Filsuf Islam: Suatu Kajian dalam Filsafat Pendidikan Islam - Sucipto Sucipto; Rachmat Panca Putera (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This research aims to examine the dialectics of Islamic philosophers’ thought within the framework of Islamic philosophy of education, focusing on the ideas of Al-Farabi, Al-Ghazali, Ibn Sina, and Ibn Khaldun. The study is motivated by contemporary issues in Islamic education, which tends to emphasize cognitive and technical aspects while neglecting spiritual, moral, and social dimensions. In this context, the intellectual heritage of classical Islamic philosophers offers alternative paradigms that are more balanced, holistic, and future-oriented. The research applies a qualitative library-based design, employing philosophical hermeneutics to interpret primary texts and secondary literature. This method allows for a critical reading of the philosophers’ ideas, followed by a synthesis of their dialectical relationships. The findings reveal three major dialectics: rationality versus spirituality, represented by Al-Farabi and Al-Ghazali; individuality versus sociality, as reflected in Ibn Sina and Ibn Khaldun; and idealism versus realism, which bridges normative visions with historical realities. These dialectics do not end in opposition but generate an integrative framework for Islamic educational philosophy. The study concludes that Islamic education should be understood as a transformative process that unites intellect and heart, balances individual growth with social responsibility, and integrates ideal visions with empirical realities. The dialectics of Islamic philosophers therefore carry not only historical significance but also strategic relevance for developing Islamic curricula oriented toward nurturing the insan kamil and fostering a dignified civilization in the global era.